Pengaruh Self Efficacy, Skeptisisme Profesional, Independensi, dan Kompleksitas TugasTerhadap Audit Judgment - Prasetya Muttiwijaya, Gede Teguh; Ariyanto, Dodik (E-Jurnal Akuntansi; Vol 27 No 2 (2019)DO - 10.24843/EJA.2019.v27.i02.p17, 2019)
The purpose of this study was to determine the effect of self efficacy, professional skepticism, independence and complexity of the task on audit judgment. This research was conducted at the Republic of Indonesia BPK Representative of the Province of Bali using a non probability sampling method with a purposive sampling technique. The total sample of this study was 57 auditors at the BPK RI in Bali province. Based on the results of this study, it is known that self efficacy, professional skepticism and independence have a positive effect on audit judgment and task complexity has a negative effect on audit judgment. The implications of this research can theoretically contribute to the development of attribution theory and are expected to be useful for all parties, especially the Republic of Indonesia BPK Representative of Bali. Keywords : Self efficacy, professional skepticism, independence, task complexity, audit judgment